2005
DOI: 10.1158/0008-5472.can-05-0949
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Differentially Regulates Migration of Tumor-Associated and Normal Human Brain Endothelial Cells

Abstract: Interleukin-8 (IL-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 44 publications
(57 reference statements)
2
51
0
Order By: Relevance
“…ELR-CXC chemokine expression could play an important role in tumor microenvironment modifications (Brat et al 2005;Charalambous et al 2005). Moreover, a previous study showed increased expression of CXCL8 in advanced cancers, which could provide an important therapeutic approach for aggressive and metastatic tumors .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…ELR-CXC chemokine expression could play an important role in tumor microenvironment modifications (Brat et al 2005;Charalambous et al 2005). Moreover, a previous study showed increased expression of CXCL8 in advanced cancers, which could provide an important therapeutic approach for aggressive and metastatic tumors .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, increased expression of ELR-CXC chemokines and their receptors has been observed in many different cancer cells, including tumor-infiltrating neutrophils, tumor-associated macrophages and endothelial cells (Brat et al 2005;Charalambous et al 2005). ELR-CXC chemokine expression could play an important role in tumor microenvironment modifications (Brat et al 2005;Charalambous et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we utilize tumor microvasculature instead of the commonly used HUVECs. We and others have shown that these 2 cell types show significant differences with respect to their phenotype 14 (Fig. 4b).…”
Section: Resultsmentioning
confidence: 62%
“…Glioblastoma-derived tumor microvascular endothelial cells (tMVECs) were purified essentially as described 14 with some modifications. Initially, the glioblastoma specimens were digested in 1 mg/ml Liberase-1 (Roche) for 10 min at room-temperature.…”
Section: Co-purification Of Tumor Microvascular Endothelial Cells Andmentioning
confidence: 99%